Marketing and promotion of quality. The public policy approach. The case of France - Paquotte P. (Global quality assessment in Mediterranean aquaculture, 2000)
In order to better answer to all challenges that the Seafood industry has at present -different supply and demand constraints- a co-ordinated and collective approach is required. Only an inter-professional approach which associates all segments of the production and distribution chain and which is both resource and market driven may be efficient. On this respect the French Ministry of Agriculture has implemented OFIMER, a National Inter-professional Office for Fisheries and Aquaculture. Quality is a good example of topic which requires a coordinated approach from the production level to the distribution level. Regarding quality, both objective and subjective aspects have to be taken into account. On the objective side, OFIMER is participating, together the professional sector and the administration, in the implementation of norms and standards, in their control, in the construction of measures and evaluation tools and in a process of product differentiation.
Workshop of the CIHEAM Networks on Technology of Aquaculture in the Mediterranean (TECAM) and Socio-Economic and Legal aspects of Aquaculture in the Mediterranean, 1999/11/29-1999/12/01, Barcelona (Spain)